Analisis Konsentrasi dan Struktur Pasar Industri Nikel Global - Hendrartono, Danang Raihan; Hendrati, Ignatia Martha; Wardaya, Wirya (Jurnal EMT KITA, 2026)
This study analyzes the level of concentration and market structure of the global nickel industry over the 2014–2023 period using a descriptive quantitative approach by calculating the Herfindahl–Hirschman Index (HHI) based on global nickel export and import data (HS 7501) sourced from TradeMap. The results indicate that the global nickel market exhibits an oligopolistic–oligopsonistic structure, characterized by the dominance of a small number of countries. The export HHI increased to 3,021 in 2023, while the import HHI reached 3,347 in the same year, confirming a strengthening concentration of market power on both the supply and demand sides. Indonesia’s dominance as the main supplier and China’s position as the largest consumer reinforce market centralization and increase the sensitivity of nickel trade to industrial policies and geopolitical dynamics. These findings are consistent with international trade theory, which emphasizes the role of market structure in shaping trade patterns of strategic commodities, and they support the Structure–Conduct–Performance (SCP) framework that explains the linkage between concentrated market structures and the strategic behavior of dominant actors. This study underscores the importance of supply diversification and strengthened international trade cooperation to mitigate dependency risks in the global nickel industry.